PkM Implementasi Tata Nilai-Nilai Integritas Akademisi berbasis Sistematika Penyuluh Antikorupsi bersama LSP P3 Pembangun Penyuluh Integritas Bangsa: Studi Kasus Pembentukan Zona Integritas di Provinsi DKI Jakarta - Dewi Puspaningtyas Faeni; Ratih Puspitaningtias Faeni; Retno Fuji Oktaviani; Ravindra Safitra Hidayat (Jurnal Nusantara Mengabdi, 2021)
Purpose: This Community Service (PKM) aimed to strengthen integrity values by taking preventive measures and promoting educational programs about the dangers of corruption, its causes, and systematic prevention. Method: This PKM was delivered to the academic community, consisting of Chancellors, Deans, Lecturers, and Students at several campuses throughout the DKI Jakarta Province. This PKM activity was made possible through the PSKK Grant (Work Competency Certification Program) under BNSP. Results: The added value of participating in the Anti-Corruption Instructor BNSP Certification Program is not only effective at systematic socialization of corruption prevention, but also serves as a Certificate of Companion Diploma (SKPI) for students, lecturers, deans, and rectors. Additionally, according to the survey’s graph, recipients of the BNSP Certificate quickly get hired.